(untitled) (Damascus University Journal of educational and Psychologyical sciences, 2025)
The research aimed to identify the degree to which school principals fulfill their roles in improving the quality of school life through social responsibility projects in primary schools from their point of view and the point of view of teachers. Measuring the differences according to the variables: (job description, number of years of experience, educational qualification). The research adopted the descriptive analytical method, and the number of the research sample reached (242) teachers and principals, and a questionnaire consisting of four axes was applied, and among the most important results of the research: The degree to which school principals carry out their roles in improving the quality of school life through social responsibility projects in primary schools from the point of view Their point of view and the point of view of the teachers in the research sample was average, and there were no significant differences according to the job description variable, and there were statistically significant differences according to the number of years of experience variable in favor of individuals who have a number of years of experience (21 years or more), and according to the academic qualification variable in favor of the sample members. Researchers who possess an academic qualification: (diploma and above).